Kneeling ability after total knee replacement. Issue 7 (7th July 2019) - Wylde, Vikki; Artz, Neil; Howells, Nick; Blom, Ashley W.
Abstract : Kneeling ability is consistently the poorest patient-rated outcome after total knee replacement (TKR), with 60–80% of patients reporting difficulty kneeling or an inability to kneel. Difficulty kneeling impacts on many activities and areas of life, including activities of daily living, self-care, leisure and social activities, religious activities, employment and getting up after a fall. Given the wide range of activities that involve kneeling, and the expectation that this will be improved with surgery, problems kneeling after TKR are a source of dissatisfaction and disappointment for many patients. Research has found that there is no association between range of motion and self-reported kneeling ability. More research is needed to understand if and how surgical factors contribute to difficulty kneeling after TKR. Discrepancies between patients' self-reported ability to kneel and observed ability suggests that patients can kneel but elect not to. Reasons for this are multifactorial, including knee pain/discomfort, numbness, fear of harming the prosthesis, co-morbidities and recommendations from health professionals. There is currently no evidence that there is any clinical reason why patients should not kneel on their replaced knee, and reasons for not kneeling could be addressed through education and rehabilitation. There has been little research to evaluate the provision of healthcare services and interventions for patients who find kneeling problematic after TKR. Increased clinical awareness of this poor outcome and research to inform the provision of services is needed to improve patient care and allow patients to return to this important activity. Cite this article: EFORT Open Rev 2019;4:460-467. DOI: 10.1302/2058-5241.4.180085